Efficacy of acupuncture on upper limb dysfunction after stroke: a randomized controlled trial protocol with surface electromyography evaluation - Liying Wang; Zining Guo; Jiewen Zhang; Run Lin; Xiaorong Tang; Cui Gao; Shaoyang Cui; Nenggui Xu (Frontiers in Medicine)
BackgroundUpper extremity functional reconstruction remains a major clinical challenge in post-stroke neurorehabilitation. Acupuncture has unique advantages as a complementary alternative therapy. Thus, in this study, we aim to compare sham acupuncture to reveal the efficacy and safety of acupuncture in the treatment of upper limb dysfunction post-stroke with surface electromyography (sEMG), a validated objective assessment tool, and a subjective index.MethodsIn this prospective, principal-investigator-blinded randomized controlled trial, 74 patients who meet the inclusion criteria are randomly assigned to the acupuncture and sham acupuncture groups in a 1:1 ratio using a central randomization system. The patients receive the same routine basic treatment. The core acupoints selected in the acupuncture group are GV20 (Bai hui), DU14 (Da zhui), and LI11 (Qu chi). Six non-meridian acupuncture points are selected for the sham acupuncture group. The treatment cycle lasts for 4 weeks, five times per week, for 20 treatments. The Fugl–Meyer Upper Limb Assessment scale score is used as the main outcome. Secondary outcomes include the Motor Status Scale, Action Research Arm Test, Motor Assessment Scale, Self-rating Anxiety Scale, and Self-rating Depression Scale scores. Simultaneously using sEMG as an auxiliary efficacy indicator.ConclusionThis study assesses the effectiveness and safety of acupuncture for post-stroke upper limb impairment in multiple aspects and elucidates the underlying neuromuscular effect mechanism of acupuncture to provide clinical evidence.RegistrationInternational Traditional Medicine Clinical Trials Registry. Registration No. ITMCTR2025000228. November 27, 2024. The study was approved by the Ethics Committee of Guangzhou University of Traditional Chinese Medicine, Shenzhen Hospital (Futian), Ethics. No. GZYLL (KY)-2024–045-01. November 13, 2024.